Application of forecasting methods in business - Šečkute, Laima; Pabedinskaite, Arnoldina (Journal of Business Economics and Management, 2003)
In order to provide Lithuanian enterprises with methodical recommendations regarding forecasting, the authors of this article have analysed the advantages and limitations of various forecasting methods. The problem of the accuracy of business forecasts is considered in greater detail, and the practical ways of doing the evaluation and assurance of the accuracy of the forecasting methods under discussion are presented here. The authors of the article suggest that an integrated forecasting model should be applied as it is much more accurate than any forecasting that is provided by the mentioned methods when taken separately. This will help to reduce the cost of forecasting, which is of utmost importance to Lithuanian businesses.First Published Online: 14 Oct 2010